Rice Straw Composting by Lignocellulytic Microorganisms for Improved Stability and Bioefficacy in Sclerotial Disease Suppression - Hossain, Md. Kausar (2011)
Rice (Oryza sativa L.) is an important cereal crop in the world. Annually, a huge amount of rice straw (RST) is produced as by-product of rice cultivation. Proper disposal of RST is a concern across the world. Composting is an alternative for recycling of RST into a useful product. Composting of RST however is time consuming as it comprises of lignocellulosic material. Therefore, in the present study, the ability of a lignocellulolytic microbial consortium (Aspergillus niger and Trichoderma viride) at different pH conditions as activator and enhancer of maturity and stability of RST compost was evaluated, and its bioefficacy against sclerotial foot rot of chilli was determined. A total of 125 microbes were isolated from different in-situ and in-vitro RST compost sources. Twenty lignocellulolytic microbial isolates (5-bacteria, 5- actinobacteria and 10-fungi) were selected based on enzymatic degradation of starch,cellulose and lignin, followed by screening for adaptability on rice straw powder (RSP)-amended media. Six isolates (B37, A7, F26, F28, F29 and F44) were selected as lignocellulolytic agents for in-vitro RST biodegradation based on their optimum growth rate, biomass production and lignocellulolytic activities on RSP-amended media. Fungal isolates were found to be more efficient than bacteria and actinobacteria in terms of decomposing cellulose, hemicellulose, and lignin, and total carbon during RST biodegradation. Four fungal isolates (F26, F28, F29 and F44) were evaluated for their in-vitro compatibility. Six different interactions were found between the four interacting fungal isolates in the form of mutual intermingling, partial mutual intermingling and inhibition at the contact point. Finally, a consortium of A. niger (F44) and T. viride (F26) was selected as the best potential lignocellulolytic microbial consortium for rapid composting of RST. Compost stability and maturity were determined by monitoring the physical, biochemical and biological changes during composting. The RST compost produced was termed as microbial infused RST compost was also tested for its bioefficacy in terms of seed germination and seedling establishment, plant growth and disease suppression in chilli under plant house condition. Composting of RST amended with lignocellulolytic microbial consortium (A. niger and T. viride) under natural (pH 6.75) pH condition showed significant changes in terms of physical, biochemical and biological parameters compared to acidic (pH 5.75) and alkaline (pH 7.75) pH conditions. After day 21, microbial consortium under natural pH condition was found to reduce C/N ratio to 17.5 from an initial value of 29.2 and increased germination index to 75.5. The remaining lignin and cellulose contents in microbial infused RST compost were 9.8 and 12.4%, respectively. Enzymatic activities namely, ᵝ-1,4-endo-glucanase,ᵝ-1,4-exo-glucanase and total dehydrogenase activity were significantly lower than noninoculated treatments. The contents of N, P, K, Ca and Mg were 2.3, 1.1, 2.6, 2.5 and 1.4%, respectively. These results suggest that, after day 21, microbial infused RST compost produced under natural pH could be used as a substitute for inorganic fertilizers. Under plant house condition, it was found that application of microbial infused RST compost significantly increased seed germination, plant growth and suppressed the development of foot rot caused by S. rolfsii in chilli compared to commercial compost (BFC, CMT Agro Resources Sdn Bhd) or the use of fungicide Benomyl. Application at a rate of 15 t/ha was optimum for seed germination and seedling establishment, plant growth and disease suppression suggesting that microbial infused RST compost could be used as an alternative to chemical fungicide Benomyl for the control of sclerotial disease in chilli.